Impact Of Geographic Variation On Physicochemical Properties Of Neem (Azadirachta Indica) Seed Oil - Sandanasamy, Jessinta; Azhari, H. Nour; Saiful Nizam, Tajuddin; Nour, A. H. (IJPSR, 2014)
The applications of the seed oil are defined by its quality through many factors, including seed origin. The study aims to investigate the physicochemical characteristics to compare the oil quality of plant Azadirachta indica(Family: Meliaceae), grown in different geographical areas, Malaysia and Sudan. Oils were extracted through Soxhlet method via hexane for the duration of 6 h. The characteristics of the oils from Malaysia (OMY) and Sudan (OSD) are; lipid content: 37.03 and 39.96%; physical state: liquid for both; color: greenish brown and brownish yellow; odor: peanut with garlic and only peanut; density: 0.95 and 1.06 g/cm3 ; refractive index: 70.90 and 69.80; pH: 4 and 5; moisture & volatile matter: 0.83 and 0.07%; acid value: 4.80 and 6.37 mg KOH/g; iodine value: 93.09 and 63.81 gI2/100g; peroxide value: 8.49 and 1.67 meq O2/kg; unsaponifiable matter: 1.84 and 0.91%; and free fatty acid: 4.75 and 3.21%. OMY and OSD recorded eight similar fatty acids: oleic- 20.46 and 52.02%, linoleic- 34.69 and 3.02%, stearic- 20.42 and 18.79%, palmitic- 18.66 and 20.79%, arachidic- 3.59 and 2.39%, behenic- 0.80 and 0.41%, lignoceric- 0.55 and 0.27%, and palmiticoleic acid 0.17 and 0.27%, respectively. Myristic-(0.05%) and lauric acid (0.02%) were found only in OSD. No significant differences observed in transmittance. These oils showed suitable characteristics for applications as non-drying oils, whereby the OSD has fewer tendencies towards oxidative rancidity. The overall study proves that, the plant geographical variation influences the quality of the oil.